Evaluation of the Antioxidant Activity of Betula pendula Leaves Extract and its Effects on Model Foods - Nurul Aini, Mohd Azman; Skowyra, Monika; Muhammad, Kwenstan; Gallego, Maria Gabriela; Almajano, Maria Pilar (Taylor & Francis, 2017)
Context: Betula pendula Roth (Betulaceae) exhibits many pharmacological activities in humans including anticancer, antibacterial, and antiviral effects. However, the antioxidant activity of BP towards lipid degradation has not been fully determined. Objective: The BP ethanol and methanol extracts were evaluated to determine antioxidant activity by an in vitro method and lyophilized extract of BP was added to beef patties to study oxidative stability. Materials and methods: Antioxidant activities of extracts of BP were determined by measuring scavenging radical activity against methoxy radical generated by Fenton reaction 2,20-azino-bis-3-ethylbenzothiazoline- 6-sulphonic acid (TEAC) radical cation, the oxygen radical absorbance capacity (ORAC) and the ferric reducing antioxidant power (FRAP) assays. The lipid deterioration in beef patties containing 0.1% and 0.3% (w/w) of lyophilized extract of BP stored in 80:20 (v/v) O2:CO2 modified atmosphere (MAP) at 4 C for 10 days was determined using thiobarbituric acid reacting substances (TBARS), % metmyoglobin and colour value. Results: The BP methanol extract revealed the presence of catechin, myricetin, quercetin, naringenin, and p-coumaric acid. The BP ethanol (50% w/w) extract showed scavenging activity in TEAC, ORAC and FRAP assays with values of 1.45, 2.81, 1.52mmol Trolox equivalents (TE)/g DW, respectively. Reductions in lipid oxidation were found in samples treated with lyophilized BP extract (0.1% and 0.3% w/w) as manifested by the changes of colour and metmyoglobin concentration. A preliminary study film with BP showed retard degradation of lipid in muscle food. Conclusion: The present results indicated that the BP extracts can be used as natural food antioxidants.